2014
DOI: 10.1097/hjh.0000000000000080
|View full text |Cite
|
Sign up to set email alerts
|

The effects of weight loss and salt reduction on visit-to-visit blood pressure variability

Abstract: Objectives As evidence suggests visit-to-visit variability (VVV) of blood pressure (BP) is associated with cardiovascular events and mortality, there is increasing interest in identifying interventions that reduce VVV of BP. We investigated the effects of weight loss and sodium reduction, alone or in combination, on VVV of BP in participants enrolled in phase II of the Trials of Hypertension Prevention. Methods BP readings were taken at 6-month intervals for 36 months in 1,820 participants with high-normal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Fourth, the study was not designed as a long-term study and patients were followed up for one week only. Although it is generally accepted that long-term salt restriction leads to reductions in BP levels and variability, one study reported that salt restriction over 36 months did not decrease visit-to-visit BP variability [ 29 ]. Fifth, short-term glycemic control status may have affected BP parameters in some way, given the STOP-NIDDM study finding that long-term glycemic control leads to reductions in the incidence of hypertension [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the study was not designed as a long-term study and patients were followed up for one week only. Although it is generally accepted that long-term salt restriction leads to reductions in BP levels and variability, one study reported that salt restriction over 36 months did not decrease visit-to-visit BP variability [ 29 ]. Fifth, short-term glycemic control status may have affected BP parameters in some way, given the STOP-NIDDM study finding that long-term glycemic control leads to reductions in the incidence of hypertension [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Four studies assessed the relationship between salt intake and BP. Diaz and colleagues conducted an RCT investigating the effects of weight loss and salt reduction on visit‐to‐visit (VVV) BP variability. VVV of BP was defined as the standard deviation of BP across six follow‐up visits.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the inverse association between urinary sodium excretion and visit-to-visit BP variability may be due to reverse causality. An intervention study reported that weight reduction and salt reduction did not reduce visit-to-visit BP variability of persons with high normal DBP [25].…”
Section: Discussionmentioning
confidence: 99%